2021
DOI: 10.1007/jhep05(2021)219
|View full text |Cite
|
Sign up to set email alerts
|

Two paths towards precision at a very high energy lepton collider

Abstract: We illustrate the potential of a very high energy lepton collider (from 10 to 30 TeV center of mass energy) to explore new physics indirectly in the vector boson fusion double Higgs production process and in direct diboson production at high energy. Double Higgs production is found to be sensitive to the anomalous Higgs trilinear coupling at the percent level, and to the Higgs compositeness ξ parameter at the per mille or sub-per mille level thanks to the measurement of the cross-section in the di-Higgs high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(94 citation statements)
references
References 36 publications
2
92
0
Order By: Relevance
“…a MuC is effectively a high-luminosity vector boson collider [46]. With this, and the fact that vector boson fusion (VBF) processes grow with energy, one can use a MuC to study Higgs couplings [47][48][49]. It has also been shown that a MuC can discover the new physics behind the (g − 2) µ anomaly [50][51][52][53], assuming that the current running experiments at Fermilab [54] and JPARC [55] establish the (g − 2) µ excess as a source of new physics.…”
Section: Jhep06(2021)133mentioning
confidence: 99%
“…a MuC is effectively a high-luminosity vector boson collider [46]. With this, and the fact that vector boson fusion (VBF) processes grow with energy, one can use a MuC to study Higgs couplings [47][48][49]. It has also been shown that a MuC can discover the new physics behind the (g − 2) µ anomaly [50][51][52][53], assuming that the current running experiments at Fermilab [54] and JPARC [55] establish the (g − 2) µ excess as a source of new physics.…”
Section: Jhep06(2021)133mentioning
confidence: 99%
“…Thanks to the technological development [21], a renewed idea that has recently gathered much momentum is the option of a high-energy muon collider that could reach the multi-(tens of) TeV regime with very high luminosity [22][23][24]. It has been demonstrated in the recent literature that a highenergy muon collider has great potential for new physics searches at the energy frontier from direct µ + µ − annihilation and a broad reach for new physics from the rich partonic channels [25][26][27][28][29], as well as precision measurements for SM physics [30] and beyond [31][32][33][34][35][36][37][38][39]. Of particular importance is the connection between the muon collider expectation and the tantalizing hint for new physics from the muon g − 2 measurement [40,41].…”
Section: Jhep12(2021)162mentioning
confidence: 99%
“…[3][4][5][6]), and by precise measurements of ElectroWeak (EW) scale processes exploiting the high luminosity of virtual vector bosons pairs (see e.g. [6][7][8]). By these two search modes, the VHEL reach on new physics is generally comparable to that of the most ambitious future collider projects, in the corresponding domains of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…At a VHEL, however, there also exists a third strategy of investigation [1,7], based on hard processes with energy scale comparable to the collider energy E cm ∼ 10 TeV. As the indirect effects of new heavy particles are enhanced at high energy, these processes are extremely sensitive probes of new physics.…”
Section: Introductionmentioning
confidence: 99%